ASPHYXIAL DEATH DUETO PLASTIC BAG SUFFOCATION,AN UNUSUAL METHOD OF COMMITTING SUICIDE IN INDIA:A CASE REPORT & REVIEW OF LITERATURE (Journal of Forensic Medicine & Toxicology, 2018)
Asphyxial suicide due to plastic bag suffocation by placing a plastic bag over the head is an unusual method of committing suicide in India. As per our knowledge death due to plastic bag suffocation is not reported in India so  far. Asphyxial suicide and even accidental deaths by plastic bag suffocation in combination with inhalation of inert gases is not uncommon worldwide other than India. Even accidental deaths by plastic bag suffocation are not  uncommon worldwide but suicide by only plastic bag suffocation is not common. In this article we report a case of suicidal asphyxiation of 24 years aged young male who committed suicide by placing a plastic bag over the head  inside a locked car, parked in the multilevel parking of the Indira Gandhi International Airport, New Delhi, India. He was an unemployed youth working as part-time driver  of his father’s taxi. The time chosen for the suicide was very odd hours in the night between 2.0 am to 5.0 am. The police investigation found no porn materials in the car and circumstantial evidences alleged no accidental or  and circumstantial evidences alleged no accidental or homicidal intentions. The autopsy was carried out in the mortuary of VMMC & Safdarjung Hospital, New Delhi. The autopsy excluded signs of any struggle and any disease.
Keywords: Plastic bag; Suicide; Asphyxia; Suffocation; Accidental Death; Autoerotic Asphyxiation.